The Contradictions of Platform Urbanism: the Role of Corporate Property Managers in the Vacation Rental Market of Milan - Conte, Veronica; Anselmi, Guido (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
Over the last decades, cities have been targeted by massive investments by technology corporations. This process, defined as the “urbanization of technology capital” (Sadowski 2020), has evolved, moving from the affirmation of the smart city paradigm to the urbanization of “platform capitalism” (Srnicek 2017) and sharing economy agendas. While the former was led by a number of big corporations providing new services to city governments, the latter are driven by a range of digital intermediaries (i.e. platforms) delivering consumer services (e.g. food, mobility, dwellings). Today, we see that both phenomena have a significant impact on the built environment and real estate dynamics, thereby affecting the city in terms of access to basic services and housing. Hence, regardless of the initial claims that digital platforms are fair, sustainable and equitable, scholars are trying to move toward an understanding of the extent to which platforms create a new marketplace, thus opening up new avenues for the circulation of capital and the extraction of rents for transnational capital. In order to assess whether digital platforms act as democratic and sustainable innovations or are simply another channel for capital accumulation, in this paper we present our work on Airbnb, global leader in the holiday rental market. We show that the platform, initially promoted within the framework of the sharing economy, over the years has created a new marketplace, turning holiday rentals into “another asset class” (van Loon and Aalbers 2017) for both individual and corporate investors. We analyze Milan, a secondary node in the network of transnational real estate capital which is rapidly globalizing leveraging sharing city agendas and local tourism. We employ a mixed method strategy combining in-depth case study, digital ethnography and computational analysis. We show that the holiday rental market mediated through Airbnb has led to a very unequal distribution of revenues and a strong concentration of earnings in the hands of a reduced number of corporate players. Through these exploratory results we seek to contribute to the discussion on market regulation in contexts characterized by competitive growth agendas (Cox 1993), an increasing monopolistic power of tech/financial actors (Anselmi et al 2021), and the need to adopt more sustainable and just housing policies.